Mathematics Curriculum Review in Senior High School Using Curriculum Review Mapping System (CRMS) - Fatimah Rahmawati; Iin Habibah Muttaqin; Maman Fathurrohman; Ihsanudin Ihsanudin (International Journal on Emerging Mathematics Education, 2021)
Curriculum 2013 that is currently being implemented in Indonesia, still holds many obstacles in its implementation. One of them is the constraints in making a lesson plan. Some tools can help teachers create better lesson plans, one of which is a tool called Curriculum Review Mapping System (CRMS). This research aims to find out the results of national curriculum analysis in mathematics in high school using CRMS and also teacher response to these results. This study used descriptive methods with a qualitative approach. The instruments used are documentation, interviews, and researchers themselves. CRMS uses a technology called a mapping system to analyze the curriculum. The description of the national curriculum analysis results is contained in the result and discussion section. CRMS can be used as a teacher lesson plan analysis tool as teacher preparation before the teacher presents his/her learning in the classroom.